The level of emotional intelligence among Saudi nursing students: A cross-sectional study - Ahmed Mansour Almansour (Belitung Nursing Journal, 2023)
Background: Emotional intelligence is an individual’s capacity to comprehend, use, and control their own emotions to communicate and connect with people successfully. The emotional intelligence level among nursing students indicates their ability to regulate their emotions, possess self-awareness, demonstrate empathy, have motivation, and display social skills, impacting how they adapt during their education and preparation for nursing care. However, studies investigating emotional intelligence in the Saudi Arabian context are scarce. Objective: This study aimed to evaluate the degree of emotional intelligence and its differences according to sociodemographic variables among nursing students in Saudi Arabia. Methods: A cross-sectional study was undertaken with 322 nursing students conveniently selected at Majmaah University, Saudi Arabia. Data were collected between May and June 2023 utilizing the Schutte Self-Report Emotional Intelligence Test (SSEIT). Descriptive statistics, such as mean, standard deviation, frequency, and percentage, independent t-test, and one-way ANOVA were used for data analysis. Results: Most of the students had emotional intelligence levels ranging from moderate to high (96.6%). There were significant differences in emotional intelligence levels according to the age of students, gender, year of study, marital status, mother’s education, physical and psychological health, and grade point average (p <0.05). Conclusion: The study findings may offer valuable insights for nursing educators in universities, emphasizing the importance of enhancing emotional intelligence and integrating it into nursing curricula. Additionally, it highlights the need to develop effective strategies and training sessions and workshops according to sociodemographic factors to enhance emotional intelligence levels among nursing students.